PREVALENCE OF HEART RHYTHM DISORDERS IN THE ACUTE PERIOD OF MYOCARDIAL INFARCTION ACCORDING TO ECHOCARDIOGRAPHIC DATA - Khasanjanova F.O; Saidov M.A; Nizamov X.Sh; Abdivaliev B.K (Scholar Express Journals, 2023)
In this scientific work The prevalence of cardiac arrhythmias in the acute period of myocardial infarction was studied according to echocardiography data. The study included 55 patients diagnosed with acute coronary syndrome (ACS) with further transformation into AMI with a Q wave (35 b-x) or without a Q wave (20 b-x) , hospitalized in the departments of coronary heart disease and AMI of the Samarkand Regional Branch of the Republican specialized scientific and practical medical center of cardiology (SRF RSNPMCC). According to the results, it can be seen that the deterioration of HRV parameters is more typical for patients with pronounced changes in the echogeometry of the heart in the form of dilatation of the heart cavities with the phenomena of diastolic and systolic myocardial dysfunction, which are typical for patients with AMI with a Q wave .
Keywords: myocardial infarction; cardiac arrhythmia